Differential mass evacuation sampling technique for measuring refrigerant charge and oil retention of round tube plate fin heat exchangers (ASHRAE RP-1785). (2nd July 2020) - Lee, Abraham J.; Bach, Christian K.; Bradshaw, Craig R.
Abstract : Equipment reliability, efficiency, charge migration, and refrigerant charge optimization of refrigeration systems has been widely emphasized as critical development focus. Numerous modeling tools are utilized to predict charge of oil and refrigerant in refrigeration systems during system design. However, there is a lack of experimental validation data to confirm the accuracy of these models. The sampling technique presented in this paper allows the separate measurement of refrigerant and oil charge. An accompanying heat exchanger volume measurement technique was utilized to estimate heat exchanger volume and required measurement accuracy. The high accuracy, simple, and comparatively fast measurement technique enables collection of high-fidelity experimental data efficiently, to be used to validate charge models. Key components which are crucial to implement the technique include a removable heat exchanger charge test module and a modular duct assembly. A test plan using a Box-Behnken design of experiments was developed that maximizes test effort effectiveness by minimizing the number of tests required for thorough model validation.